Supply chain contract design considering the supplier's asset structure and capital constraints. (November 2019) - Lin, Qiang; He, Jinying
Highlights: We obtain the bank interest rate considering the supplier's asset structure. We study the influence of supplier's asset structure on the supply chain strategies. The optimal contract selection under different conditions is obtained. The choice of the contract is related to the market environment. Abstract: This paper investigates the influence of supplier's asset structure in financing strategies on an extended supply chain with one retailer, one capital-constraint supplier, and one bank, where the retailer acts as a leader. Three financing strategies are considered: bank financing (BF), a guaranteed contract with a buy-back clause (GBB), and a guaranteed contract with a wholesale price discount clause (GWD). We find that if the supplier has an adequate asset structure, the supplier can increase profits for both sides of the supply chain. We obtain interest rates under BF and a guaranteed contract. Furthermore, the choice of the contract is related to the market environment, and we find the threshold for contract selection. Through a comparison, we show that a GWD contract is a better financing strategy under exuberant market demand. Finally, we provide concrete numerical examples to verify the impact of the supplier's asset structure and contract parameters on the profits and financing model selection of both parties in the supply chain.